2003
DOI: 10.1262/jrd.49.485
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postpartum Endometritis and the Effect of Endometritis on Reproductive Performance in Dairy Cows in Korea

Abstract: Abstract. The objectives of this study were to determine the risk factors for postpartum endometritis by evaluating several reproductive factors in individual cows, and to determine the effect of endometritis on the subsequent reproductive performance in dairy herds in Korea. The data, including health status, parity and body condition score (BCS) of cows, and calving date, were collected from 320 cows in eight dairy herds calving from January 2001 to October 2002. We used logistic regression to evaluate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 42 publications
5
49
0
6
Order By: Relevance
“…These results show more frequent toxaemia in cows with putrid lochia compared to cows with purulent lochia. External symptoms of toxaemia such as lassitude, anorexia, drop in milk yield and dehydratation are not sufficiently accurate because they are present only in some cases (Nakao et al, 1992;Hirvonen et al, 1999;Huszenicza et al, 1999;LeBlanc et al, 2002b;Kim and Kang, 2003;Maizon et al, 2004;Gilbert et al, 2005;Sheldon et al, 2006). In accordance with the literature mentioned, in our trial these symptoms were found only sporadically.…”
Section: Discussionsupporting
confidence: 55%
“…These results show more frequent toxaemia in cows with putrid lochia compared to cows with purulent lochia. External symptoms of toxaemia such as lassitude, anorexia, drop in milk yield and dehydratation are not sufficiently accurate because they are present only in some cases (Nakao et al, 1992;Hirvonen et al, 1999;Huszenicza et al, 1999;LeBlanc et al, 2002b;Kim and Kang, 2003;Maizon et al, 2004;Gilbert et al, 2005;Sheldon et al, 2006). In accordance with the literature mentioned, in our trial these symptoms were found only sporadically.…”
Section: Discussionsupporting
confidence: 55%
“…However, cows that cannot eliminate the infection may subsequently develop endometritis [4]. Various risk factors, such as calving problems, a retained placenta, metabolic disorders, and the parity or nutritional status of the cow have been related to the development of postpartum endometritis, although some of them are controversial [5][6][7][8][9][10][11][12][13]. Since many dairy cows experience sudden nutritional and endocrine changes during the peripartum period [14,15], this may lead to aberrant immune function that could predispose the cows to severe uterine infections [16].…”
mentioning
confidence: 99%
“…This situation could probably be attributed to either weak uterine defense mechanism or poor immune status of the cow. Other factors such as, poor hygiene and stress of housing and management (Kim and Kang, 2003) could also play a role in development of SCE during the late postpartum period.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of bacterial pathogens in the uterus of cows suffering from SCE has been attributed to various factors during and after calving (Markusfeld, 1987;Hussain et al, 1990;Kim and Kang, 2003). In view of this, a clinical study was designed with the objective to determine common aerobic pathogens associated with postpartum subclinical endometritis in crossbred dairy cows.…”
Section: Introductionmentioning
confidence: 99%